Implementasi Program Kebijakan Pengelolaan Penyakit Kronis (PROLANIS) di Puskesmas Kassi-kassi Kota Makassar - Azzahra Khaerun Nisa; Arni Rizqiani Rusydi; Reza Aril Ahri (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Global mortality is largely caused by non-communicable diseases, with approximately 41 million deaths annually. In an effort to address this problem, the government, through the BPJS Kesehatan (Social Security Agency for Health), initiated the Chronic Disease Management Program (PROLANIS). This study aims to determine the implementation of PROLANIS at the Kassi-Kassi Community Health Center (Puskesmas), Makassar City. This study is descriptive and qualitative. The study included 18 informants: PROLANIS participants, the Head of the Puskesmas, and PROLANIS officers. Data collection was conducted through in-depth interviews and observations. Data validity was guaranteed through triangulation of sources and techniques. Data analysis was conducted qualitatively through the stages of data reduction, data presentation in narrative and matrix form, and conclusion. The results of the study indicate that the implementation of PROLANIS at the Kassi-Kassi Community Health Center, in terms of communication, resources, disposition, and bureaucratic structure, is quite good but not optimal and still requires improvement, especially in service quantity. Therefore, it is recommended that the Puskesmas improve information dissemination and emphasize participants' commitment to the program.